Bond states, moiré patterns, and bandgap modulation of two-dimensional BN/SiC van der Waals heterostructures. Issue 5 (9th July 2020) - Bo, Maolin; Li, Hanze; Deng, Anlin; Li, Lei; Yao, Chuang; Huang, Zhongkai; Peng, Cheng
Abstract : This study aims to determine moiré patterns on the two-dimensional (2D) BN/SiC heterojunction at lattice strains of 5% and 7% and different incident angles, which can be applied to photoelectric detection technology. Abstract : The matched lattice strain of the graphene/hexagonal boron nitride (BN) heterojunction that is less than 2% is known to form a moiré pattern. However, in the BN/SiC heterojunction, the formation of a moiré pattern for a lattice strain more than 5% is a novel phenomenon. This study aims to determine moiré patterns on the BN/SiC heterojunction at lattice strains of 5% and 7% and different incident angles, which can be applied to photoelectric detection technology. The BN/SiC-1 and BN/SiC-2 heterojunctions formed in this study had bandgaps of 0.851 and 1.373 eV, respectively. Furthermore, we observed that when two BN/SiC heterojunctions have indirect bandgaps, the BN/SiC van der Waals heterojunction can be a potential photoelectric material. We analyze the bonding states using the bond-charge model and calculate the potential functions of the antibonding, bonding, and nonbonding states. This study provides a theoretical reference for the precise regulation of the charge density and chemical bonding states of the 2D material surface.